I don’t know I just need points lol
Answer:
Heyyy!!!!
The answer is 1.
Please read explanation it will definitely help you....
Step-by-step explanation:
Okay... Here it goes...
Basically, there is an exponent rule that says that anything to the power of 0 is 1.
I hope this helps!
Given:
Positions of two artifacts are at points (1, 4) and (5, 2).
To find:
The distance between these two artifacts.
Solution:
Distance formula: The distance between two points is
![d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28x_2-x_1%29%5E2%2B%28y_2-y_1%29%5E2%7D)
Using distance formula, the distance between two points (1, 4) and (5, 2) is
![d=\sqrt{(5-1)^2+(2-4)^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%285-1%29%5E2%2B%282-4%29%5E2%7D)
![d=\sqrt{(4)^2+(-2)^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%284%29%5E2%2B%28-2%29%5E2%7D)
![d=\sqrt{16+4}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B16%2B4%7D)
![d=\sqrt{20}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B20%7D)
![d=4.4721359](https://tex.z-dn.net/?f=d%3D4.4721359)
Round to the nearest tenth of a unit.
![d\approx 4.5](https://tex.z-dn.net/?f=d%5Capprox%204.5)
Therefore, the distance between two artifacts is 4.5 units.
Answer: my childhood Memories
We're going on a trip in our favorite rocket ship
Zooming through the sky, Little Einsteins
the black/hood verse
"We're going on to the club in our favorite range rover
Zooming through the hood, Little gangsta's"
Answer:
![(f\cdot g)(x)=2x^2+10x+12](https://tex.z-dn.net/?f=%28f%5Ccdot%20g%29%28x%29%3D2x%5E2%2B10x%2B12)
![(f-g)(x)=-x-1](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D-x-1)
![(f+g)(1)=10](https://tex.z-dn.net/?f=%28f%2Bg%29%281%29%3D10)
Step-by-step explanation:
![\tt f(x)=x+3](https://tex.z-dn.net/?f=%5Ctt%20f%28x%29%3Dx%2B3)
![\tt g(x)=2x+4](https://tex.z-dn.net/?f=%5Ctt%20g%28x%29%3D2x%2B4)
![(f\cdot g)(x)=f(x)\cdot g(x)=(x+3)(2x+4)=2x^2+4x+6x+12](https://tex.z-dn.net/?f=%28f%5Ccdot%20g%29%28x%29%3Df%28x%29%5Ccdot%20g%28x%29%3D%28x%2B3%29%282x%2B4%29%3D2x%5E2%2B4x%2B6x%2B12)
![=2x^2+10x+12](https://tex.z-dn.net/?f=%3D2x%5E2%2B10x%2B12)
![(f-g)(x)=f(x)-g(x)=x+3-(2x+4)=x+3-2x-4](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3Df%28x%29-g%28x%29%3Dx%2B3-%282x%2B4%29%3Dx%2B3-2x-4)
![=-x-1](https://tex.z-dn.net/?f=%3D-x-1)
![(f+g)(1)=f(1)+g(1)=1+3+2(1)+4](https://tex.z-dn.net/?f=%28f%2Bg%29%281%29%3Df%281%29%2Bg%281%29%3D1%2B3%2B2%281%29%2B4)
![=4+2+4=10](https://tex.z-dn.net/?f=%3D4%2B2%2B4%3D10)
~